Alcohol Consumption Before and After Breast Cancer Diagnosis: Associations With Survival From Breast Cancer, Cardiovascular Disease, and Other Causes - Newcomb, Polly A. (American Society of Clinical Oncology, 2013)
PURPOSE: Alcohol intake is associated with increased risk of breast cancer. In contrast, the relation between alcohol consumption and breast cancer survival is less clear. PATIENTS AND METHODS: We assessed pre- and postdiagnostic alcohol intake in a cohort of 22,890 women with incident invasive breast cancer who were residents of Wisconsin, Massachusetts, or New Hampshire and diagnosed from 198 to 200 at ages 20 to 79 years. All women reported on prediagnostic intake; a subsample of 4,881 reported on postdiagnostic intake. RESULTS: During a median follow-up of 11.3 years from diagnosis, 7,780 deaths occurred, including 3,484 resulting from breast cancer. Hazard ratios (HR) and 95% CIs were estimated. Based on a quadratic analysis, moderate alcohol consumption before diagnosis was modestly associated with disease-specific survival (compared with nondrinkers, HR = 0.93 [95% CI, 0.85 to 1.02], 0.85 [95% CI, 0.75 to 0.95], 0.88 [95% CI, 0.75 to 1.02], and 0.89 [95% CI, 0.77 to 1.04] for two or more, three to six, seven to nine, and ≥ 10 drinks/wk, respectively). Alcohol consumption after diagnosis was not associated with disease-specific survival (compared with nondrinkers, HR = 0.88 [95% CI, 0.61 to 1.27], 0.80 [95% CI, 0.49 to 1.32], 1.01 [95% CI, 0.55 to 1.87], and 0.83 [95% CI, 0.45 to 1.54] for two or more, three to six, seven to nine, and ≥ 10 drinks/wk, respectively). Results did not vary by beverage type. Women consuming moderate levels of alcohol, either before or after diagnosis, experienced better cardiovascular and overall survival than nondrinkers. CONCLUSION: Overall alcohol consumption before diagnosis was not associated with disease-specific survival, but we found a suggestion favoring moderate consumption. There was no evidence for an association with postdiagnosis alcohol intake and breast cancer survival. This study, however, does provide support for a benefit of limited alcohol intake for cardiovascular and overall survival in women with breast cancer.